Report of the Committee Examining Radiation Risks of Internal Emitters (CERRIE) (London, 2004)
"Tougher action is needed to allow for new information about the risks from internal radiation. Uncertainties about the risks mean that in some cases we might be exposed to 10 times the risk previously thought, while in other cases the risk may be almost zero. Uncertainties in current methods of estimating risks from internal radiation require policy makers and regulators to adopt a precautionary approach when dealing with exposures to internal radiation, according to a Report published today by the Committee Examining Radiation Risks of Internal Emitters (CERRIE). The Report advises that greater attention should be paid to these uncertainties. The Report warns also that newly discovered effects of radiation, genomic instability (ongoing, long-term increase in mutations within cells and their offspring), bystander effects (cells next to those that were irradiated can also be damaged), and minisatellite mutations (inherited germline DNA changes) are real biological events that need further research. However the Report finds no clear evidence to date that current radiation risks are substantially wrong. The Committee was established by the then Environment Minister in 2001 following concerns about the health risks of internal radiation, including reports of increased incidences of cancer near nuclear sites and after Chernobyl. ..."